BUILDING AWARENESS OF RELIGIOUS EDUCATION IN FAMILIES IN THE DIGITAL AGE - Heru Pratikno (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
In this digital era, the importance of religion in family and school is still underestimated. Parents prioritize general education over religion for their children. So, it is not a surprise there are children who are good in an area of expertise such as math, yet they doesn’t show decency towards their friends, siblings, other people, or even their own parents. Good moral has to begin from the use of language for interactions. Therefore, this research has the purpose of explaining how to apply politeness in language use in family that is compatible with Islamic education. Beside, how to implement polite language in digital learning. The writer used references study to collect data. Other than that, the author used qualitative descriptive analysis as the method of data analyzing. This research shows that family is the first and main environment to apply good and polite use of language that is compatible with Islamic education. In a family, parents are supposed to actively guide children to be polite in using language to create Islamic character within children. AbstrakPada era digital ini, kesadaran akan pentingnya pendidikan agama di lingkungan keluarga dan sekolah masih dianggap remeh. Para orang tua lebih mengedepankan pendidikan umum untuk anak-anaknya daripada pendidikan agama. Jadi, kita tak heran jika terdapat anak yang pandai dalam bidang tertentu, seperti mahir matematika, tetapi sang anak tidak memiliki akhlak yang baik kepada teman, saudara, orang lain, atau bahkan orang tuanya sendiri. Akhlak yang baik itu harus dimulai dari penggunaan bahasa ketika berinteraksi. Oleh karena itu, penelitian ini memiliki tujuan untuk menjelaskan bagaimanakah cara menerapkan kesantunan berbahasa di lingkungan keluarga yang sesuai dengan pendidikan agama Islam. Selain itu, bagaimana implementasi berbahasa santun dalam pembelajaran digital. Metode penelitian yang digunakan penulis untuk mengumpulkan data adalah studi pustaka. Selain itu, penulis menggunakan metode kualitatif deskriptif untuk menganalisis data. Hasil penelitian ini menunjukkan bahwa keluarga merupakan lingkungan pertama dan utama dalam penerapan penggunaan bahasa yang baik dan santun sesuai pendidikan agama Islam. Dalam lingkungan keluarga, orang tualah yang sangat berperan aktif dalam melatih dan mencontohkan anak untuk berbahasa yang santun demi membentuk karakter anak yang berakhlak Islami.